45.3: Invited Paper: Going Towards High‐Resolution, Uniform AMOLED Displays with a High Brightness Range. (26th August 2021) - Verschueren, Lynn; Ameys, Marc; Lopez, Mauricio Velazquez; Glushkova, Anastasia; Nag, Manoj; Smout, Steve; Ke, Tung Huei; Vandenplas, Erwin; Kronemeijer, Auke Jisk; Heremans, Paul; Genoe, Jan; Dehaene, Wim; et al.
Abstract : Going towards high‐resolution, uniform displays with a high‐brightness range requires optimizations on different topics. This work presents an overview on this subject. To achieve a good uniformity, a compensation method is proposed using a 2T1C pixel circuit, compatible with high‐resolution requirements, improving uniformity by a factor 52.5. In order to further increase the achievable resolution, a new technology stack, using a planar and a vertical TFT is introduced. For increasing the brightness range, a global dimming method, compatible with the 2T1C pixel circuit, is demonstrated.